Sport managers in Finland - Seppänen, Kari-Pekka (2020)
The purpose of this Master’s thesis is to study the profiles of the sport managers in Finland at the moment. More specifically the research aim to investigate to what extent the sport manager types defined by Laakso (2016) can be applied in the sport management field in general. For this purpose, a quantitative survey was conducted. An email-survey was sent to 633 managers working in leading sport positions in different sport organizations in Finland. In total 284 answers were received resulting in a response rate of 44.9 percent.